Variations of soil thermal conductivity in the Three-River Source Region, Qinghai‒Xizang Plateau - Jia Liu; Dong-Liang Luo; Wen-Jie Lei; Fang-Fang Chen; Rui-Xia He; Cheng-Song Yang; Yan Lu; Shi-Zhen Li (Advances in Climate Change Research)
The ongoing permafrost degradation in the Three-River Source Region (TRSR) poses serious threats to ecosystems, water resources, and infrastructure projects. As the China Water Tower and a vital barrier for the high-altitude ecological security of China, the TRSR is particularly vulnerable to such changes. The extent and severity of permafrost degradation are primarily governed by heat transfer dynamics, with soil thermal conductivity (STC) playing a crucial role in regulating thermal equilibrium. However, research on STC is hindered by insufficient in-situ measurements. To address this gap, we conducted in-situ measurements of STC at soil depths of 0–40 cm across 58 plots at 12 sites in the TRSR (244 records) during July and August 2023. The driving mechanisms influencing STC variations were further analyzed through laboratory experiments in September and October 2023. Spatially, STC increases from west to east and vertically with soil depth. Control experiments revealed that STC at negative temperatures is markedly higher than that at positive temperatures and increases with volumetric moisture content, particularly in inorganic soils, sand and loamy sand. This effect is more pronounced at subzero temperatures. Meanwhile, our results show that an artificial neural network model (R2 = 0.78, p < 0.0001) incorporating ten measured soil physical parameters, outperforms traditional theoretical and empirical models in predicting STC. These findings contribute to a deeper understanding of permafrost formation, evolution, and its responses to climate change in the TRSR.